PEMANFAATAN BOTOL BEKAS UNTUK MEDIA TANAMAN HIDROPONIK DI KELURAHAN BAMBU KUNING KOTA PEKANBARU - Rini Nizar; Seprita Lidar; Khairunnas Khairunnas (UIN Sunan Kalijaga, 2022)
Plastic bottle waste is one type of inorganic waste that is difficult to decompose naturally. The use of this bottle is increasing and most of it comes from households. This waste if not managed properly will have an impact on the environment, but if used properly it will have added value. This was requested by head mother of RW 01 Bambu Kuning Village, utilizing plastic bottle waste into useful and value-added products. The purpose of this activity is to increase the knowledge and skills of housewives about recycling plastic bottle waste as a planting medium for hydroponic cultivation so that it can contribute to environmental cleanliness. This community service activity is carried out by (ABCD) Asset Based Community Development. This activity involved the Lecturer Team of the Faculty of Agriculture, Lancang Kuning University, hydroponic practitioners and administrators of the women's group in the neighborhood in RW 01, Bambu Kuning Village. This activity succeeded in increasing the knowledge and skills of hoisewives in hydroponic cultivation using bottle waste.